Turoctocog alfa is safe for the treatment of Indian patients with hemophilia A: Guardian 10 trial results. Issue 8 (22nd October 2020) - John, M. Joseph; Chakrabarti, Prantar; Apte, Shashikant; Bhattacharyya, Maitreyee; S., Chandrakala; Hansen, Trine; Kolla, Rohan; Ross, Cecil; Seth, Tulika; Siddharthan, Neeraj; Abraham, Aby
Abstract: Background: Hemophilia A is an X chromosome–linked bleeding disorder caused by the deficiency of coagulation factor VIII (FVIII). The majority of the Indian population with hemophilia A use plasma‐derived clotting factors and, in some instances, fresh frozen plasma and cryoprecipitate. Safer and more efficient treatment options are needed for this group of patients. Objectives: To assess the safety of turoctocog alfa, a third‐generation recombinant FVIII molecule, for the treatment and prophylaxis of bleeding episodes in previously treated Indian patients with moderate or severe hemophilia A. Patients/Methods: This single‐country, multicenter, open‐label, nonrandomized trial enrolled 60 patients who received prophylactic treatment with turoctocog alfa for 8 weeks, which corresponded to a minimum of 20 exposure days. Confirmed development of FVIII inhibitors during the 8‐week treatment period was evaluated. Other assessments included frequencies of adverse drug reactions (ARs), serious adverse reactions, drug‐related allergic reactions, and infusion reactions during the 12‐week period after the first treatment; hemostatic effect of turoctocog alfa for the treatment of bleeding episodes; and total annualized dose of turoctocog alfa administered during the 8‐week treatment period. Results: No incidence of FVIII inhibitors was detected. No safety concerns such as ARs, serious ARs, or drug‐related allergic reactions were noted. The hemostatic success rate for the treatment of bleeding episodes with turoctocog alfa was 81.6%. Conclusions: The trial results demonstrated that turoctocog alfa is a safe treatment option for the prophylaxis and treatment of bleeding episodes in previously treated adolescent and adult patients with hemophilia A in the Indian population.